Plectin-mediated cytoskeletal crosstalk controls cell tension and cohesion in epithelial sheets - Prechova, Magdalena; Adamova, Zuzana; Schweizer, Anna Lena; Maninova, Miloslava; Bauer, Andreas; Kah, Delf-Thorge Eric; Meier-Menches, Samuel M.; Wiche, Gerhard; Fabry, Ben; Gregor, Martin (The Journal of Cell Biology, 2022)
The coordinated interplay of cytoskeletal networks critically determines tissue biomechanics and structural integrity. Here, we show that plectin, a major intermediate filament-based cytolinker protein, orchestrates cortical cytoskeletal networks in epithelial sheets to support intercellular junctions. By combining CRISPR/Cas9-based gene editing and pharmacological inhibition, we demonstrate that in an F-actin-dependent context, plectin is essential for the formation of the circumferential keratin rim, organization of radial keratin spokes, and desmosomal patterning. In the absence of plectin-mediated cytoskeletal cross-linking, the aberrant keratin-desmosome (DSM)-network feeds back to the actin cytoskeleton, which results in elevated actomyosin contractility. Also, by complementing a predictive mechanical model with Förster resonance energy transfer-based tension sensors, we provide evidence that in the absence of cytoskeletal cross-linking, major intercellular junctions (adherens junctions and DSMs) are under intrinsically generated tensile stress. Defective cytoarchitecture and tensional disequilibrium result in reduced intercellular cohesion, associated with general destabilization of plectin-deficient sheets upon mechanical stress.
CRIS-Team Scopus Importer:2022-03-04